Mobilising the 'People's Army' at the Grassroots: Examining Support for the UK Independence Party (UKIP) in English Local Elections. Issue 2 (11th April 2018) - Thrasher, Michael; Goodwin, Matthew J; Rallings, Colin; Borisyuk, Galina
Abstract: Between 2013 and the referendum on Britain's EU membership in 2016, the UK Independence Party (UKIP) emerged as the most significant new party in English politics for a generation. Yet, despite rising to become the third most popular party, temporarily replacing the Liberal Democrats in the polls, UKIP failed to translate support into a large presence in Westminster. At the 2015 general election, the party won only one seat and in the aftermath of the 2016 referendum suffered a major loss of support. In this article, we investigate UKIP's rise and show why the party's evolution at local level is an important but neglected factor in its failure to engineer a substantial breakthrough. By analysing aggregate-level data on local elections and surveys of UKIP's largely inexperienced but enthusiastic candidates, we show how the party's initial advance came largely at the expense of the Conservative Party but then opened a second front against Labour, in more urban areas. Unlike the Liberal Democrats, UKIP was unable to sustain this momentum and failed to use a local government base as a foundation for strong representation in parliament.